2010
DOI: 10.1007/s00018-010-0476-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal cells and MMP13 contribute to experimental choroidal neovascularization

Abstract: In this study, we evaluate the potential involvement of collagenase--3 (MMP13), a matrix metalloproteinase (MMP) family member, in the exudative form of age--related macular degeneration (AMD) characterized by a neovascularisation into the choroid. RT--PCR analysis revealed that human neovascular membranes issued from patients with DMLA expressed high levels of Mmp13. The contribution of MMP13 in choroidal neovascularization (CNV) formation was explored by using a murine model of laser--induced CNV and applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
1
30
0
2
Order By: Relevance
“…Both neutrophil and macrophage depletion reduce CNV formation [14][15][16] . The recruitment of BM-derived cells (endothelial progenitor cells, pericytes, mesenchymal stem cells) in CNV lesions has been reported 5,[17][18][19] and mimics the vasculogenic process observed in human patients 17 . Vascular endothelial growth factor (VEGF-A) rapidly emerged as a potent angiogenic factor involved in CNV formation, diverting much of the focus of research.…”
Section: Development Of the Cnv Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Both neutrophil and macrophage depletion reduce CNV formation [14][15][16] . The recruitment of BM-derived cells (endothelial progenitor cells, pericytes, mesenchymal stem cells) in CNV lesions has been reported 5,[17][18][19] and mimics the vasculogenic process observed in human patients 17 . Vascular endothelial growth factor (VEGF-A) rapidly emerged as a potent angiogenic factor involved in CNV formation, diverting much of the focus of research.…”
Section: Development Of the Cnv Assaymentioning
confidence: 99%
“…Transgenic mouse technologies have since allowed rapid expansion in the exploration of key regulators of CNV, leading to the identification of other important VEGF family members, such as placental growth factor (PlGF) 23,24 and proteases 19,[25][26][27][28] . More recently, the interplay between complement factor H, the complement membrane attack complex, a chemokine (CCL2) and VEGF during CNV development has been established 29,30 .…”
Section: Development Of the Cnv Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, stem cell research has been mainly based on in vitro studies, postmortem histological analysis or molecular biology experiments [2,15,16]. In the present study, molecular imaging using the Fluc reporter gene and D -luciferin reporter probe can be used as a dynamic and reproducible in vivo imaging method of stem cell survival in CNV lesions in a mouse model.…”
Section: Discussionmentioning
confidence: 98%
“…It's the leading cause of irreversible blindness in the western countries and the rate is continuously going up because of the rapid increasing of averaged age (Kolar, 2010). Generally, AMD is classified as dry or nonexudative AMD and wet or neovascular AMD, according to the presence or the absence of Neovascularization (NV Lecomte et al, 2011). Some studies showed that nearly 50% of cells in the new vessels were GFP positive, indicating they arise from bone-marrow.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%